2003
DOI: 10.1001/archinte.163.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proximal Adenomatous Polyps With Screening Sigmoidoscopy

Abstract: Distal adenomatous polyps, including diminutive distal adenomatous polyps, are associated with an increased prevalence of synchronous proximal neoplasia. Two percent to 5% of patients undergoing screening colonoscopy may have isolated advanced proximal neoplasia. Even more patients may have isolated nonadvanced proximal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…The clinical implications of this concept include the need for colonoscopy in patients with adenoma detected on flexible sigmoidoscopy (increased risk of synchronous lesions) or previous colonoscopy (metachronous lesions). 20 There have been numerous markers of field carcinogenesis in the predysplastic mucosa, including proteomic, 21 genomic, 22 methylation 23 and microRNA. 24 The most common markers for chemoprevention studies have been the reversal of the diffuse increase in proliferation and inhibition of apoptosis.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…The clinical implications of this concept include the need for colonoscopy in patients with adenoma detected on flexible sigmoidoscopy (increased risk of synchronous lesions) or previous colonoscopy (metachronous lesions). 20 There have been numerous markers of field carcinogenesis in the predysplastic mucosa, including proteomic, 21 genomic, 22 methylation 23 and microRNA. 24 The most common markers for chemoprevention studies have been the reversal of the diffuse increase in proliferation and inhibition of apoptosis.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…In addition, individuals without adenomas in the distal colon, as shown by sigmoidoscopy, frequently do not receive a follow-up colonoscopy. The percentage of asymptomatic individuals with isolated advanced proximal adenomas or cancer who undergo a colonoscopy is 1.3–5% [58,59]. Atkin et al [60] reported that sigmoidoscopy screening reduces the mortality from CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Existe una asociación clara entre la presencia de adenomas distales y adenomas proximales. Dicha asociación puede variar en función del tamaño de la muestra cribada, en la inclusión de pacientes con historia familiar de cán-cer de colon (27) y, fundamentalmente, si se define el colon distal como la porción intestinal que puede visualizarse mediante una sigmoidoscopia o bien el segmento de colon cuyo límite superior es el ángulo esplénico (28,29). La prevalencia de neoplasias avanzadas proximales en nuestros pacientes y la probabilidad de tener adenomas en el colon distal son similares a los descritos en los estudios mencionados.…”
Section: Discussionunclassified